2017
DOI: 10.1007/s12223-017-0524-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of antimicrobial and immunomodulatory substances produced by heterofermentative Lactobacillus reuteri

Abstract: Antimicrobial and immunomodulatory potential of various Lactobacillus reuteri strains is closely connected to their metabolite production profile under given cultivation conditions. We determined the in vitro production of antimicrobial substances such as organic acids, ethanol, and reuterin by four strains of L. reuteri (L. reuteri E, L. reuteri KO5, L. reuteri CCM 3625, and L. reuteri ATCC 55730). All studied L. reuteri strains showed the ability to produce lactic acid, acetic acid, and ethanol with concomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 49 publications
1
33
0
1
Order By: Relevance
“…L. reuteri in general are fermentative lactic acid bacteria, producing many acids and metabolites under fermentative conditions including lactic acid, acetic acid and in the presence of glycerol can produce reuterin, where its antimicrobial and anti‐inflammatory effects have previously been described . However, since there was no glycerol present in these experiments, we do not attribute this inhibitory effect to reuterin but to organic acids, and other compounds which have been previously characterized in L. reuteri DSM 17938 …”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…L. reuteri in general are fermentative lactic acid bacteria, producing many acids and metabolites under fermentative conditions including lactic acid, acetic acid and in the presence of glycerol can produce reuterin, where its antimicrobial and anti‐inflammatory effects have previously been described . However, since there was no glycerol present in these experiments, we do not attribute this inhibitory effect to reuterin but to organic acids, and other compounds which have been previously characterized in L. reuteri DSM 17938 …”
Section: Discussionmentioning
confidence: 78%
“…[53] However, since there was no glycerol present in these experiments, we do not attribute this inhibitory effect to reuterin but to organic acids, and other compounds which have been previously characterized in L. reuteri DSM 17938. [54][55][56] Although many bacterial species such as C. acnes and S. epidermidis are found as part of the normal flora and are involved in maintaining healthy skin and protection from invading pathogens, [52,57] the relationship between microorganisms co-inhabiting the skin is complex and it has been shown that in some cases commensal bacteria can be implicated in certain skin conditions, such as acne. [8,58] Other research studies have demonstrated that invading bacteria can exacerbate some skin conditions, such as S. pyogenes which is a significant pathogen involved in soft tissue infections and impetigo.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have shown that L reuteri cell‐free supernatant was as effective in inhibiting P gingivalis as living bacteria, suggesting that microbial growth reduction was mainly due to the substances produced by the probiotic. Besides reuterin, L reuteri strains produce a series of other antimicrobial substances, including lactic acid, acetic acid, ethanol, and reutericyclin . The literature has also shown the importance of the acidic environment in the interactions between L reuteri and other microorganisms .…”
Section: Discussionmentioning
confidence: 99%
“…Besides reuterin, L reuteri strains produce a series of other antimicrobial substances, including lactic acid, acetic acid, ethanol, and reutericyclin. 3,31,32 The literature has also shown the importance of the acidic environment in the interactions between L reuteri and other microorganisms. 33 Additional well-studied metabolites such as histamine, vitamins, and exopolysaccharides contribute to L reuteri probiotic action and can be found in the culture supernatant.…”
Section: Discussionmentioning
confidence: 99%
“…This was a confirmation that the antimicrobial activity of lactobacilli is caused not only by the production of organicacids. Greifová et al (2017) reported about high antibacterial potential of four L. reuteri strains against E. coli CCM 3988 and P. aeruginosa CCM 3955 due to the production of organic acids, ethanol, and reuterin. In contrast to these results, other authors comparing of antimicrobial activity of supernatants of several probiotics (L. acidophilus, L. lactis, L. casei and L. reuteri, grown in absence or in presence of prebiotics) against E. coli have showed that the L. reuteri supernatant exhibits the least antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%